The Implementation of Foreign Language Learning Guidance Program for Elementary School Students During School Holidays - Tri Wahyudi Ramdhan; M.Tohir; Zainal Hakim; Moh Holil Baitaputra (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This community service activity is a learning assistance program that focuses on foreign language learning guidance for school-age children in the Glintong Dalam Village environment during semester holidays. With this activity, the children have interesting activities to improve their Arabic and English skills. This activity is one of the agendas of the facilitators of the Community Service Course of the Tarbiyah Faculty of STAI Darul Hikmahin 2024 in Glintong village. The service activities in the form of a foreign language learning guidance program which were attended by approximately 20 students went smoothly. The result of this activity is that the children are eager to learn Arabic and English and can overcome the difficulties they face when learning Arabic and English at school. In its implementation, children can learn calmly, comfortably, enthusiastically and are able to understand the material presented. This activity also received a positive response from themselves, parents, and the community.